Membran Polieugenol Tersulfonasi (PET) Sebagai Potensi Sel Bahan Bakar Metanol Langsung - Muliawati, Eka Cahya; Yustia Wulandari Mirzayanti (Journal of Research and Technology, 2021)
Nafion is a type of perfluorosulfonic acid membranes, are widely used in fuel cell technology and exhibit several disadvantages such as expensive, have a limited working temperature range and high methanol crossover. This study aims to produce an electrolyte new polymer membrane from polyeugenol sulfonated (PET) and a review of the membrane properties was carried out on the basis of Water Contact Angle (Â°), Water Uptake (%), Methanol Uptake (%), Swelling ratio (%), IEC (ion exchange capacity). Analysis of DMFC membrane performance has an optimal proton conductivity of 0.0009 S.cm-1 and methanol permeability of 23.5.10-7 cm2.s-1 with a PET composition of 27% (w/w). Â